1998
DOI: 10.1002/hep.510270204
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of sleep disturbance in cirrhosis

Abstract: Sleep disturbance is a classic sign of hepatic encephalopathy. However, there are limited data regarding its prevalence in cirrhotic patients without overt hepatic encephalopathy. We assessed the characteristics of sleep in cirrhosis using a sleep questionnaire (n ‫؍‬ 44) and actigraphy (n ‫؍‬ 20). The results were compared with those of subjects with chronic renal failure and those of healthy controls. Presence of subclinical hepatic encephalopathy, chronotypology profile, and individual's affective state wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
210
3
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(232 citation statements)
references
References 38 publications
12
210
3
5
Order By: Relevance
“…[52][53][54][55][56] Studies have confirmed higher frequency of sleep disturbances in patients of cirrhosis with MHE compared to those without MHE. 11,52 Sleep is maintained by two processes namely, 'Homeostatic process' that determines sleep propensity in relation to waking hours and 'Circadian process' under the control of suprachiasmatic nucleus and its retino-hypothalamic axis which responds to light-dark cues by melatonin secretion. 57 Patients with cirrhosis have unsatisfactory night sleep due to delayed sleep onset and multiple night awakenings resulting in reduced sleep time and excessive daytime sleepiness.…”
Section: Sleep and Health Related Quality Of Lifementioning
confidence: 95%
See 1 more Smart Citation
“…[52][53][54][55][56] Studies have confirmed higher frequency of sleep disturbances in patients of cirrhosis with MHE compared to those without MHE. 11,52 Sleep is maintained by two processes namely, 'Homeostatic process' that determines sleep propensity in relation to waking hours and 'Circadian process' under the control of suprachiasmatic nucleus and its retino-hypothalamic axis which responds to light-dark cues by melatonin secretion. 57 Patients with cirrhosis have unsatisfactory night sleep due to delayed sleep onset and multiple night awakenings resulting in reduced sleep time and excessive daytime sleepiness.…”
Section: Sleep and Health Related Quality Of Lifementioning
confidence: 95%
“…57 Night time sleep disturbances are not related to HE and are caused by circadian rhythm abnormalities due to toxic effect on suprachiasmatic nucleus and impaired melatonin clearance. 52 However, excessive daytime sleepiness correlates with ammonia levels and is associated with increased risk of HE related hospitalization and presence of portosystemic shunts. 58 Sleep disturbances contribute to impairment in HRQOL in MHE patients.…”
Section: Sleep and Health Related Quality Of Lifementioning
confidence: 99%
“…Sleep disturbance and excessive daytime somnolence are common in patients with cirrhosis [1,2,3,4]. In addition, a disturbance of sleep is recognized as one of the early signs of hepatic encephalopathy [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The most common feature of the sleep pattern in patients with cirrhosis is fragmented nocturnal sleep caused by frequent nocturnal awakenings, and a daytime functioning affected by frequent episodes of undesired sleepiness and more prolonged napping time [1,2]. The sleep-wake cycle was also shifted with activity toward the later hours of the day.…”
Section: Introductionmentioning
confidence: 99%
“…While there is evidence for this in animal models, human studies provide a considerably more heterogeneous picture. [22][23][24][25][26] This may be due to a number of factors, including cultural and environmental confounders, the heterogeneity of the patient populations studied, and a certain tendency of hepato-gastroenterologists and internists to group all kinds of sleep disturbances together, and to study them with tools such as quality of life and psychological well-being questionnaires. 23 In more recent years, some work has been devoted to defining the sleepwake disturbances exhibited by these patients in a more formal, systematic fashion, in collaboration with sleep scientists and chronobiologists.…”
Section: Sleepiness and Hepatic Encephalopathymentioning
confidence: 99%